Modeling of electrical behavior of La0.7Ca0.3MnO 3 ceramic using impedance spectroscopy - Kumar V.; Thakur O.P.; Pandey L.; Guimaraes A.P.; Goel A.; Parkash O.; Kumar D. (My University, 2025)
The ceramic system La0.7Ca0.3MnO3 was prepared by solid state method and impedance measurements were carried out as a function of frequency (100 Hz-1 MHz) in the temperature range 303-529 K. An equivalent circuit model that represented the data well was arrived at by comparing the experimental plots with computer simulated complex immittance spectra of model circuits. It consisted of three parallel RC circuits connected in series indicating the presence of three processes present in the system. The resistances are found to follow the behavior R = R0 exp(E/kT). The values of activation energy E for these are obtained. © World Scientific Publishing Company.